THE PHONOMENON OF A MIRACLE CURE IN RELIGION AND THE FINE ARTS - Gudonis, Vytautas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper deals with the evolution of votive offering as the expression of praying for health and the gratitude for a miracle cure from ancient times to the present day. The tradition of votive offerings, as the means of asking for health and receiving a miracle cure, goes for thousands of years.The article analyses the question if the votive offering tradition has been continued in Lithuanian churches and if any known facts about a miracle cure have been found in the 21st century. The aim of this research is to detect the continuation of the votive offerings in Lithuanian churches. Interviews and content analysis have been used as research methods. Information collected from interviewing 5 worshipers and 19 priests in Lithuania. Unique examples of a miracle cure have been depicted. Votive offerings have been analysed as a part of rich cultural heritage. The diversity of votive offerings has been detected and depicted in the fine arts. The tradition of votive offering is viewed as the expression of the belief in a miracle cure. The assumption has been made that the placebo effect is present in a miracle cure. The findings suggest that the tradition of votive offerings still exist and being practiced in Lithuanian churches nowadays.